What You Fight for Shapes How You Fight. (2021) - Fazal, Tanisha M.
Abstract : The question of where to begin when considering the conditions under which states and non-state actors comply with international humanitarian law (IHL) is itself an interesting one because of the history of IHL. IHL was created by states, principally to govern their behavior in relation to each other. The major codified elements of IHL, such as the 1949 Geneva Conventions, are agreements signed by states. For the last several decades, however, most wars have occurred within, rather than between, states. This trend raises the question of whether and when armed non-state actors (ANSAs, typically called "rebel groups" by political scientists) might comply with IHL.